Tetranucleotide and Low Microsatellite Instability Are Inversely Associated with the CpG Island Methylator Phenotype in Colorectal Cancer - Meessen, Sabine (Cancers (Basel), 2021)
SIMPLE SUMMARY: A type of DNA mismatch repair defect known as “elevated microsatellite alterations at selected tetranucleotide repeats” (EMAST) is found across many different cancers. Tetranucleotide microsatellite instability, which is caused by MSH3 mismatch repair gene/protein loss-of-function, shares a molecular basis with “low microsatellite instability” (MSI-L) in colorectal cancer. Tetranucleotide microsatellite instability is also a byproduct of “high microsatellite instability” (MSI-H) that arises from deficiency of mismatch repair due to MSH2, MSH6, MLH1 or PMS2 gene alterations. MSH3-related EMAST is emerging as a biomarker of poor prognosis in colorectal cancer and needs to be clearly differentiated from MSI-H. Here, we show that tumours with non-MSI-H-related EMAST or MSI-L rarely show concordant promoter methylation of multiple marker genes. Colorectal tumours that are positive for a single (1/5) tetranucleotide repeat marker are an important subset of the EMAST spectrum. ABSTRACT: MSH3 gene or protein deficiency or loss-of-function in colorectal cancer can cause a DNA mismatch repair defect known as “elevated microsatellite alterations at selected tetranucleotide repeats” (EMAST). A high percentage of MSI-H tumors exhibit EMAST, while MSI-L is also linked with EMAST. However, the distribution of CpG island methylator phenotype (CIMP) within the EMAST spectrum is not known. Five tetranucleotide repeat and five MSI markers were used to classify 100 sporadic colorectal tumours for EMAST, MSI-H and MSI-L according to the number of unstable markers detected. Promoter methylation was determined using methylation-specific PCR for MSH3, MCC, CDKN2A (p16) and five CIMP marker genes. EMAST was found in 55% of sporadic colorectal carcinomas. Carcinomas with only one positive marker (EMAST-1/5, 26%) were associated with advanced tumour stage, increased lymph node metastasis, MSI-L and lack of CIMP-H. EMAST-2/5 (16%) carcinomas displayed some methylation but MSI was rare. Carcinomas with ≥3 positive EMAST markers (13%) were more likely to have a proximal colon location and be MSI-H and CIMP-H. Our study suggests that EMAST/MSI-L is a valuable prognostic and predictive marker for colorectal carcinomas that do not display the high methylation phenotype CIMP-H.